1971
DOI: 10.1007/bf02431967
|View full text |Cite
|
Sign up to set email alerts
|

The state of water in the outer barrier of the isolated frog skin

Abstract: The flux of water across the outer barrier of the frog skin is generally regarded as the rate-limiting step in the movement of water across the whole membrane. This paper presents some evidence that, at room temperature, the flux of water across the outer barrier occurs through water in a non-liquid state. The organization of water in a non-liquid state lowers the diffusion coefficient of water through water by several orders of magnitude. The study employs a method recently developed in this laboratory which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This issue was not tested rigorously in the present experiments , since, for the reasons indicated previously, permeation coefficients were measured only at two temperatures. However, a similar assumption has been made by Hays et al [-22] in evaluating the effect of ADH on the EA for water diffusion in toad urinary bladder; and, both in frog skin [18] and in rabbit gall bladder [51], water permeation appears to follow a linear Arrhenius relationship for the temperature range 21-39 ~ Given this caveat, Tables 2 and 3 summarize the results for simultaneous measurements of the apparent activation energies for water and n-butyr- amide permeation. In the absence of ADH (Table 2), E A was 9.35_+0.92 and 19.40 _+ 1.6 kcal per mole for, respectively, Py and n-butyramide permeation; the mean paired difference between these two values was 7.7 + 0.74 (P < 0.002).…”
Section: Apparent Activation Energies For Water and Solute Permeationmentioning
confidence: 62%
“…This issue was not tested rigorously in the present experiments , since, for the reasons indicated previously, permeation coefficients were measured only at two temperatures. However, a similar assumption has been made by Hays et al [-22] in evaluating the effect of ADH on the EA for water diffusion in toad urinary bladder; and, both in frog skin [18] and in rabbit gall bladder [51], water permeation appears to follow a linear Arrhenius relationship for the temperature range 21-39 ~ Given this caveat, Tables 2 and 3 summarize the results for simultaneous measurements of the apparent activation energies for water and n-butyr- amide permeation. In the absence of ADH (Table 2), E A was 9.35_+0.92 and 19.40 _+ 1.6 kcal per mole for, respectively, Py and n-butyramide permeation; the mean paired difference between these two values was 7.7 + 0.74 (P < 0.002).…”
Section: Apparent Activation Energies For Water and Solute Permeationmentioning
confidence: 62%
“…In preliminary experiments we noticed that, provided it is ice cold, the washing with isotonic sucrose might be continued for at least 9 sec, without changing the slope of the uptake curve. This is expectable as it was observed that the flux of water (Grigera & Cereijido, 1971) and sodium (Rodriguez Boulfin, Moreno, Rotunno & Cereijido, 1972, unpublished) (j~o and J~2 A) have a high activation energy.…”
Section: The Flux Of Sodium Across the Outer Border Of The Epitheliummentioning
confidence: 66%
“…Both values were well above the 4.6 kcal/mole reported THE JOURNAL OF GENERAL PHYSIOLOGY VOLUME 59, 1972 ' pages 519-533 by Wang et al (16) for diffusion of water in bulk solution. Such high activation energies have been explained (4)(5)(6)(7) as resulting from the extensive bonding of water with the components of the aqueous channel or from the formation of icelike structures by water within the membrane. It is not possible on the basis of the diffusion data alone to determine whether the movement of individual water molecules is primarly restrained by water-water or by water-membrane hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%